2015
DOI: 10.2141/jpsa.0130208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Ovo Administration of Branched-Chain Amino Acids on Embryo Growth and Hatching Time of Chickens

Abstract: The effect of various branched-chain amino acids (BCAA : isoleucine, leucine, valine) on embryo growth and the hatching time of fertilized eggs of chickens was examined. Before the onset of egg incubation, one of BCAA was injected into fertilized eggs. The amount of each BCAA administrated into eggs was equal to 1% of each amino acid exits in the egg. On day 14 of incubation, the weight of embryos was measured. On day 21, the hatching time was recorded, and body weight of chicks at birth was measured. The in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…The body weight at hatch, hatchability, FCR and GIT traits in the present study was comparable to that obtained by Bhanja and Mandal (2005), who used a mixture of leucine, isoleucine and valine of about 1.75:1.00:1.23 percent in amino acid injected birds. Likewise, Kita et al (2015) founded that there was no significant differences in body weight at hatch among in ovo injection of each BCAA. In the present study, the fact that the BCAA blend did not affect negatively the studied variables indicate that the dose of BCAA blend was not a level that would cause a harmful effect on these parameters, because excess BCAA in diet has detrimental effect to chicks (D'Mello and Lewis, 1970).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The body weight at hatch, hatchability, FCR and GIT traits in the present study was comparable to that obtained by Bhanja and Mandal (2005), who used a mixture of leucine, isoleucine and valine of about 1.75:1.00:1.23 percent in amino acid injected birds. Likewise, Kita et al (2015) founded that there was no significant differences in body weight at hatch among in ovo injection of each BCAA. In the present study, the fact that the BCAA blend did not affect negatively the studied variables indicate that the dose of BCAA blend was not a level that would cause a harmful effect on these parameters, because excess BCAA in diet has detrimental effect to chicks (D'Mello and Lewis, 1970).…”
Section: Resultsmentioning
confidence: 97%
“…Although it was expected that in ovo injection of the BCAA individually (Kita et al, 2015) or blend (Bhanja and Mandal, 2005) would stimulate the growth performance of broilers due to the may be related to the reported properties of the HMB and IGF-1 (Moore et al, 2005;Kornasio et al, 2009;Pedrosa et al, 2013), research on leucine, isoleucine and valine and/or blend of these yield contradicting results (Bhanja and Mandal, 2005;Kita et al, 2015). However, the results of the present study are in agreement with previous observations that indicated a mixture of BCAA that did not affect body weight gain, feed intake or feed efficiency in fast-growing broilers (Bhanja and Mandal, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations